Delayed low cerebellar perfusion status is associated with poor outcomes in top-of-basilar occlusion treated with thrombectomy - Ryu, Jae-Chan; Kwon, Boseong; Song, Yunsun; Lee, Deok Hee; Chang, Jun Young; Kang, Dong-Wha; Kwon, Sun U.; Kim, Jong S.; Kim, Bum Joon (Frontiers in Neurology, 2023)
Background and purpose Top-of-basilar artery occlusion (TOB) is one of the most devastating strokes despite successful mechanical thrombectomy (MT). We aimed to investigate the impact of initial low cerebellum perfusion delay on the outcomes of TOB treated with MT. Methods We included patients who underwent MT for TOB. Clinical and peri-procedural variables were obtained. Perfusion delay in the low cerebellum was defined as (1) time-to-maximum (Tmax) >10 s lesions or (2) relative time-to-peak (rTTP) map >9.5 s with a diameter of ≥6 mm in the low cerebellum. The good functional outcome was defined as the achievement of a modified Rankin Scale score of 0–3 at 3 months after stroke. Results Among the 42 included patients, 24 (57.1%) patients showed perfusion delay in the low cerebellum. The admission National Institutes of Health Stroke Scale (NIHSS) score was significantly higher in those with perfusion delay [17 (12–24) vs. 8 (6–15), P = 0.002]. Accordingly, the proportion of good functional outcomes was lower in those with perfusion delay than in those without [5 (20.8%) vs. 13 (72.2%), P = 0.003]. From the multivariable analysis, the admission NIHSS score [odds ratio (OR) = 0.86, 95% confidence intervals (CIs) = 0.75–0.98, P = 0.021] and low cerebellum perfusion delay (OR = 0.18, 95% Cis = 0.04–0.86, P = 0.031) were independently associated with the 3-month functional outcomes. Conclusion We found that initial perfusion delay proximal to TOB in the low cerebellum might be a predictor for poor functional outcomes in TOB treated with MT.